Optimization of ion-exchange displacement separations: I. Validation of an iterative scheme and its use as a methods development tool - Natarajan, Venkatesh; Wayne Bequette, B.; Cramer, Steven M. (Journal of Chromatography A, 2000)
Displacement chromatography has been demonstrated to be a powerful, high-resolution preparative tool. The performance of displacement systems can be affected by a variety of factors such as the feed load, flow-rate, initial salt concentration and the displacer partition ratio. Thus, the optimization of displacement separations is a uniquely challenging problem. In this manuscript, an iterative optimization scheme has been presented whereby one can identify the optimum operating conditions for displacement separations at a given level of loading on a given resin material. The solid film linear driving force model has been employed in concert with the Steric Mass Action formalism of ion-exchange chromatography to describe the chromatographic behavior in these systems. Simple pulse techniques have been employed to estimate the transport parameters. The iterative scheme has been validated using a rigorous Feasible Sequential Quadratic Programming algorithm. Finally, the utility of the iterative optimization scheme as a methods development tool for displacement separations has been demonstrated for a difficult separation. The results indicate that the use of the optimization scheme leads to significantly better performance than standard rules of thumb.